Exploring the ISO 14001 environmental management system (EMS towards SMEs organizational performance: case study of southern Malaysia furniture manufacturers - Abdul Hamid, Nor Aziati (2015)

(untitled)
Environmental issues associated with industrial activities such as gas emissions and toxic chemicals waste caused the nature imbalance effects. Therefore, IS014001 standard was introduced and employed globally. Previous studies related to IS0 14001 in Malaysia are focused at high technologies and construction sectors. Thus, this research aims to determine the correlation between IS0 14001 orientation factor and environlnental management capability (EMC) of suppliers towards SMEs organizational performance. The surveys were distributed to various IS0 14001 certified furniture manufacturing companies registered under Federation of Malaysian Manufacturers in southern region of Malaysia. The data were collected among 70 respondents at the nlanagerial and production level. Eff~cient production and EMC of suppliers' factors are significantly correlated to organizational performance. 'I'hus, companies are recommended to employed green supply chain practices and ecoefficiency production processes. This quantitative case study is important to SMEs in the specific area in order to provide knowledge on the impact of IS014001 into production and operation